Extrusion‐Printed CNT–Graphene Sensor Array with Embedded MXene/PEDOT:PSS Heater for Enhanced NO2 Sensing at Low Temperature. Issue 24 (15th November 2021) - Hassan, Kamrul; Stanley, Nathan; Tung, Tran Thanh; Yap, Pei Lay; Rastin, Hadi; Yu, Le; Losic, Dusan
Abstract: Wearable sensors are currently one of the top emerging areas with enormous growth potential. Low‐cost fabrication techniques using simple and scalable printing technologies are making a significant impact on their development. Recent advances in high‐performance gas/vapor sensors based on carbon nanomaterials have shown potential applications ranging from disease diagnostics to environmental monitoring and defences. Herein, a hybrid sensing material of 1D carbon nanotubes (CNTs) and 2D graphene is developed, and a conductive ink is formulated, which is applied for fabricating a nitrogen dioxide (NO2 ) gas sensor array within a compact design utilizing extrusion printing. To improve NO2 ‐sensing performance and optimal operating temperature, a reverse‐side layer is designed, which combines MXene and poly(3, 4‐ethylenedioxythiophene)‐doped poly(styrene sulfonate) (PEDOT:PSS), and functions as a Joule heater. The printed CNT–graphene‐based sensor with an embedded MXene/PEDOT:PSS heater is capable of detecting trace amounts of NO2 gas (1 ppm) at 65 °C. The sensor is able to distinguish between various gases/volatile organic compounds and target NO2 gas based on their chemical affinities. The printed CNT–graphene sensor array also demonstrates a high‐level of recoverability, satisfied stability, durability, and reproducibility, which render this sensor a suitable candidate for practical applications. Abstract : This work presents the development of the printable ink composed of 1D–2D hybrid carbon nanomaterials (carbon nanotube and graphene) formulated using eco‐friendly medium for 3D extrusion printing and fabrication of chemoresistive sensor arrays, with an embedded MXene/PEDOT:PSS heater capable of detecting trace amounts of NO2 gas with enhanced sensing characteristics.